Hydrogen Sulfide and Persulfides Oxidation by Biologically Relevant Oxidizing Species - Dayana Benchoam; Ernesto Cuevasanta; Matías N. Möller; Beatriz Alvarez (Antioxidants, 2019)
Hydrogen sulfide (H2S/HS⁻) can be formed in mammalian tissues and exert physiological effects. It can react with metal centers and oxidized thiol products such as disulfides (RSSR) and sulfenic acids (RSOH). Reactions with oxidized thiol products form persulfides (RSSH/RSS⁻). Persulfides have been proposed to transduce the signaling effects of H2S through the modification of critical cysteines. They are more nucleophilic and acidic than thiols and, contrary to thiols, also possess electrophilic character. In this review, we summarize the biochemistry of hydrogen sulfide and persulfides, focusing on redox aspects. We describe biologically relevant one- and two-electron oxidants and their reactions with H2S and persulfides, as well as the fates of the oxidation products. The biological implications are discussed.